Patient with spontaneous hematomas and ecchymosis - Loutayf Terán, Bernabé; Farias, Jorge; Viñuales, Estela; Barrera, Liliana; Tempelsman, Rocío (Revista del Hospital Italiano de Buenos Aires, 2011)
.